2012
DOI: 10.4021/jem112w
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Central Pontine Myelinolysis in a Type 1 Diabetic Patient With Anti-Insulin Antibody and Similar Clinical Manifestations to Autoimmune Polyglandular Syndrome

Abstract: Central pontine myelinolysis is a demyelinating disorder, which is commonly associated with the rapid correction of hyponatremia. We repot an 84-year-old type 1 diabetic woman with high level of anti-insulin antibody, who developed central pontine myelinolysis, in spite of a careful correction of hyponatremia. We believe that high level of anti-insulin antibody and similar clinical manifestations to autoimmune polygrandular syndrome such as Candidiasis, hypothyroidism, type 1 diabetes and liver cirrhosis possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 8 publications
(9 reference statements)
1
3
0
Order By: Relevance
“…Both anti-GAD ab and anti-IA2 ab were negative in cases 24, 25 and 26 in Table 2; however, they were insulin-dependent and showed the positivity for anti-TPO ab and anti-TG ab, and they were included in patients with APS3a. Our previous reports [4,[7][8][9] and present study revealed a remarkable female predominance in APS3a, which agreed with previous reports [10,11]. Among patients with autoimmune diabetes, SPIDDM was the most common type of diabetes, and the positive rate of anti-GAD ab was higher than that of anti-IA2 ab.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Both anti-GAD ab and anti-IA2 ab were negative in cases 24, 25 and 26 in Table 2; however, they were insulin-dependent and showed the positivity for anti-TPO ab and anti-TG ab, and they were included in patients with APS3a. Our previous reports [4,[7][8][9] and present study revealed a remarkable female predominance in APS3a, which agreed with previous reports [10,11]. Among patients with autoimmune diabetes, SPIDDM was the most common type of diabetes, and the positive rate of anti-GAD ab was higher than that of anti-IA2 ab.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, we defined the absence of diffuse goiter and/or primary hypothyroidism with positive anti-TPO ab or positive anti-TG ab as immunological Hashimoto thyroiditis. We also found an insulin-dependent female patient (urinary CPR < 0.3 μg/day) with positive anti-GAD antibody [9]. She has hypothyroidism treated by levothyroxine; however, both anti-TPO ab and anti-TG ab were negative.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations